PENGEMBANGAN MODUL MENULIS PUISI MODEL ACTIVE LEARNING BERBANTUAN AUDIO VISUAL PADA SISWA KELAS X SMK - Megasari, Ferika; Rahman, Elmustian (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Poetry writing learning in Vocational High Schools still faces challenges in terms of less innovative learning approaches and low student motivation. This research aims to develop a poetry writing module using Active Learning model assisted by audio visual for grade X SMK students through qualitative approach with library research method. Literature review was conducted on eight relevant studies from 2019-2025 discussing the use of audio visual media and active learning models in poetry writing learning. Research results show that module design integrating Active Learning principles with audio visual media has great potential in improving students' poetry writing skills. Previous research proved the effectiveness of audio visual media with strong correlation (rxy = 0.64) and learning motivation improvement up to 97.14%. Active Learning model enables active student participation through discussion, exploration, and collaborative practice. Audio visual media functions as creative stimulus that helps develop ideas and writing inspiration. Module feasibility can be ensured through validation by material, media, and pedagogical experts considering curriculum suitability and learning approach effectiveness. Research implications show that this module can become an innovative solution for transforming poetry writing learning in SMK and a model for developing teaching materials for other subjects. ABSTRAKPembelajaran menulis puisi di Sekolah Menengah Kejuruan masih menghadapi tantangan dalam hal pendekatan pembelajaran yang kurang inovatif dan rendahnya motivasi siswa. Penelitian ini bertujuan mengembangkan modul menulis puisi model Active Learning berbantuan audio visual untuk siswa kelas X SMK melalui pendekatan kualitatif dengan metode library research. Kajian pustaka dilakukan terhadap delapan penelitian relevan dari tahun 2019-2025 yang membahas penggunaan media audio visual dan model pembelajaran aktif dalam pembelajaran menulis puisi. Hasil penelitian menunjukkan bahwa desain modul yang mengintegrasikan prinsip Active Learning dengan media audio visual memiliki potensi besar dalam meningkatkan kemampuan menulis puisi siswa. Penelitian terdahulu membuktikan efektivitas media audio visual dengan korelasi kuat (rxy = 0,64) dan peningkatan motivasi belajar hingga 97,14%. Model Active Learning memungkinkan partisipasi aktif siswa melalui diskusi, eksplorasi, dan praktik kolaboratif. Media audio visual berfungsi sebagai stimulus kreatif yang membantu pengembangan ide dan inspirasi menulis. Kelayakan modul dapat dipastikan melalui validasi ahli materi, media, dan pedagogis dengan mempertimbangkan kesesuaian kurikulum dan efektivitas pendekatan pembelajaran. Implikasi penelitian menunjukkan bahwa modul ini dapat menjadi solusi inovatif untuk transformasi pembelajaran menulis puisi di SMK dan model pengembangan bahan ajar untuk mata pelajaran lain.